2016
DOI: 10.1155/2016/1472090
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Bone Level Evaluation after Functional Loading Around Two Different Dental Implant Designs

Abstract: Purpose. To investigate peri-implant alveolar bone changes using periapical radiographs before and after prosthetic delivery in submerged and nonsubmerged dental implants. Methods. Digital periapical films of 60 ITI Straumann nonsubmerged dental implants and 60 Xive Dentsply submerged dental implants were taken before, immediately after, and 12 and 24 weeks after the prosthetic restoration was delivered. Results. The 60-nonsubmerged dental implant group showed mean marginal bone resorption at baseline of 0.10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The lengths from the rough-smooth border of implant surfaces to the highest MBL were measured, and an average mesiodistal bone level was calculated for each implant. [23] The standard long-cone paralleling technique, used in each periapical radiograph and X-ray cone indicator, was performed to evaluate the bite on the film. The EZ Dental software calibration tool repaired the deviation in periapical films.…”
Section: Methodsmentioning
confidence: 99%
“…The lengths from the rough-smooth border of implant surfaces to the highest MBL were measured, and an average mesiodistal bone level was calculated for each implant. [23] The standard long-cone paralleling technique, used in each periapical radiograph and X-ray cone indicator, was performed to evaluate the bite on the film. The EZ Dental software calibration tool repaired the deviation in periapical films.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, it was 0.10 mm, and 24 weeks after implant placement, this rate reached 0.16 mm. While in the Xive brand, it was initially 0.16 and after 24 weeks of placement, it reached 0.41 mm, which was significantly higher compared to the ITI brand (15).…”
Section: Resultsmentioning
confidence: 75%
“…In a prospective longitudinal study, Burtscher et al observed increased marginal bone loss at mesial sites immediately and 7 years after prosthetic loading. Even Ho et al found greater marginal bone loss in distal than mesial sites, both studies suggest that factors related to the direction of the stress distribution around the neck of the implant and the occlusal forces may explain these differences. Further investigation on this topic would shed light to the identification of site‐specific factors related to marginal bone loss around dental implants.…”
Section: Discussionmentioning
confidence: 95%